2020
DOI: 10.1042/bsr20190239
|View full text |Cite
|
Sign up to set email alerts
|

The multidrug resistance can be reversed for the decrease of P-gp and LRP by inhibiting PI3K/Akt/NF-κB signal pathway in nasopharynx carcinoma

Abstract: Aim: To investigate the relationship between PI3K/Akt/NF-κB cellular signal pathway and the expression of P-gp and LRP in multidrug resistance (MDR) cell of nasopharyngeal carcinoma. Method: The PI3K, p-Akt and NF-κB/p65 as the activity of PI3K/Akt/NF-κB were detected by Western blot. The expressions of LRP and P-gp were detected by Western blot and real-time PCR. Result: The RIs of CNE/DDP group to DDP, 5-Fu, VCR, ADR and PTX were 35.04, 18.14, 24.13, 12.00 and 10.18, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…As described in Table 1 , a variety of cancers, aside from CRC and PDAC, are currently treated with 5-FU, generally in combination with systemic and targeted chemotherapy, radiotherapy and/or surgery. However, for such locations, data on resistance mechanisms are even scarcer than for digestive adenocarcinomas ( 17 , 18 ). It is, therefore, crucial to improve the understanding of the mode of action of 5-FU to identify the molecular mechanisms that may be involved in long-term 5-FU based treatment failure (recurrence and metastasis) ( 19 ) and to optimize the use of 5-FU for the management of patients with advanced digestive or extra-digestive cancers.…”
Section: Introductionmentioning
confidence: 99%
“…As described in Table 1 , a variety of cancers, aside from CRC and PDAC, are currently treated with 5-FU, generally in combination with systemic and targeted chemotherapy, radiotherapy and/or surgery. However, for such locations, data on resistance mechanisms are even scarcer than for digestive adenocarcinomas ( 17 , 18 ). It is, therefore, crucial to improve the understanding of the mode of action of 5-FU to identify the molecular mechanisms that may be involved in long-term 5-FU based treatment failure (recurrence and metastasis) ( 19 ) and to optimize the use of 5-FU for the management of patients with advanced digestive or extra-digestive cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K signalling pathway is involved in MDR in various cancers. ABC membrane transporters reduce and drug resistance can be reversed following the inhibition of the PI3K signalling pathway [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of this pathway can promote the proliferation of various tumor cells, including hepatocellular carcinoma, bladder cancer, and cervical carcinoma, inhibit tumor cell apoptosis, and resist sensitivity to radiotherapy and chemotherapy [41][42][43]. Liu et al demonstrated that inhibition of the PI3K/Akt/NF-κB signaling pathway reverses drug resistance in NPC [44]. Moreover, activation of the PI3K/Akt signaling pathway decreases the expression of the CDK inhibitors p21 and p27, thereby promoting cell cycle progression, which causes the proliferating cells to undergo uncontrollable proliferation by escaping from the regulation of p21 and p27, ultimately causing tumor progression [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%